2017
DOI: 10.1093/eurheartj/ehx448
|View full text |Cite
|
Sign up to set email alerts
|

Separate and combined associations of obesity and metabolic health with coronary heart disease: a pan-European case-cohort analysis

Abstract: Irrespective of BMI, metabolically unhealthy individuals had higher CHD risk than their healthy counterparts. Conversely, irrespective of metabolic health, overweight and obese people had higher CHD risk than lean people. These findings challenge the concept of 'metabolically healthy obesity', encouraging population-wide strategies to tackle obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
152
0
10

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(176 citation statements)
references
References 60 publications
14
152
0
10
Order By: Relevance
“…Numerous prospective cohort studies have previously investigated the association between MHO phenotype and CVDs risk as a composite outcome (7,9,11,12,13,14,15,16,25,34,39,40), whereas specific outcomes, such as MI were limited. Our results were also consistent with those of recent meta-analyses showing that MHO individuals were at increased risk for cardiovascular events over a long-term follow-up (41).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous prospective cohort studies have previously investigated the association between MHO phenotype and CVDs risk as a composite outcome (7,9,11,12,13,14,15,16,25,34,39,40), whereas specific outcomes, such as MI were limited. Our results were also consistent with those of recent meta-analyses showing that MHO individuals were at increased risk for cardiovascular events over a long-term follow-up (41).…”
Section: Discussionmentioning
confidence: 99%
“…Previous prospective cohort studies have demonstrated that MHO individuals are at an increased risk of CVDs and all-cause mortality compared with metabolically healthy normal weight (MH-NW) individuals (7,9,11,12,13,14,15). For example, a recent large-scale study investigating a 30-year follow-up period in 90 257 women found that the MHO group had an increased 1.44-fold risk of MI, 1.37-fold risk of stroke and 1.39-fold risk of CVDs (15).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to BMI, the criteria used to define subgroups in the context of metabolic health is frequently based on: (1) the absence/ presence of the metabolic syndrome; and (2) insulin sensitivity. Interestingly, findings from several meta-analyses [8][9][10][11] and recent large-scale cohort studies [12][13][14] do not clearly support the notion that MHO subgroups, as currently defined, are protected from cardiometabolic complications ( Table 1).…”
Section: Evidence For An Mho Phenotypementioning
confidence: 95%
“…However, among individuals with CVD events, the metabolic syndrome has been found to be present in a much smaller fraction of individuals with normal weight as compared with overweight and obese individuals. As an example, in the European Prospective Investigation into Cancer and Nutrition (EPIC-CVD) study, only 20% of incident CVD cases among normal-weight participants were observed in those with the metabolic syndrome at baseline; this is a considerably smaller proportion than in overweight (52%) and obese (76%) individuals [14]. This clearly points towards variation in the sensitivity of the metabolic syndrome to predict future CVD cases across the BMI range; its absence is unlikely to rule out CVD risk in normal-weight individuals.…”
Section: The Muhnw Phenotypementioning
confidence: 99%
“…Early reports suggested that individuals with MHO were not at increased risk of CVD compared with individuals with metabolically healthy normal weight (4,5). However, several recent prospective cohort studies have found an increased CVD risk associated with MHO (3,(27)(28)(29)(30)(31)(32). A prospective cohort study in the U.K. consisting of 3.5 million adults with a median follow-up time of 5.4 years showed that MHO was associated with CVD compared with metabolically healthy normal weight (30).…”
Section: Comparison With Other Studiesmentioning
confidence: 99%